Pengaruh Jarak Zinnia elegans Dengan Kedelai (Glycine max) Terhadap Kelimpahan Musuh Alami dan Serangan Hama, West Aceh - Putri Mustika Sari; Oviana Lisa; Sumeinika Fitria Lizmah; Rayhan Amadius Weihan; Dewi Andriani (Politeknik Negeri Lampung., 2025)
This study was conducted to determine the effect of Zinnia elegans plant spacing as a refugiaplant on the abundance of natural enemies and the level of pest attacks on soybean (Glycinemax). The study used a non-factorial Randomized Block Design (RBD) with five treatments:no refugia (J0), and plant spacing of 40 cm (J1), 60 cm (J2), 80 cm (J3), and 100 cm (J4),each with four replications. The parameters observed included the identification andpopulation of natural enemy insects, the abundance of natural enemy insects, the area andintensity of pest attacks. Data analysis was carried out using analysis of variance andcontinued with the LSD test at the 5% level. The results showed that the 40 cm plant spacing(J1) was the most effective treatment, resulting in the highest abundance of natural enemies(31 individuals from 4 families) and the lowest pest population (2 individuals). Treatment J1also showed the lowest pest attack area (5.47%) and very light attack intensity (3.62%),while the control (J0) showed an attack area of 23.47% and an attack intensity of 19.42%,which is classified as moderate. The high abundance of natural enemies at a plantingdistance of 40 cm indicates the effectiveness of refugia in creating microhabitats that supportnatural predators in the soybean planting ecosystem. These data indicate that the use ofZinnia elegans refugia at optimal planting distances can suppress pest attacks whileincreasing soybean plant productivity. Therefore, the integration of refugia plants withappropriate planting distances can be an effective, environmentally friendly biologicalcontrol strategy and support sustainable agriculture.